Rotation curve fitting and its fatal attraction to cores in realistically simulated galaxy observations - Pineda, Juan C. B.; Springel, Volker (Arxiv, 2016)
We study the role of systematic effects in observational studies of the cusp-core problem under the minimum disc approximation using a suite of high-resolution (25-pc softening length) hydrodynamical simulations of dwarf galaxies. We mimic realistic kinematic observations and fit the mock rotation curves with two analytic models commonly used to differentiate cores from cusps in the dark matter distribution. We find that the cored pseudo-isothermal sphere (ISO) model is strongly favoured by the reduced $χ^2_ν$ of the fits in spite of the fact that our simulations contain cuspy Navarro-Frenk-White profiles (NFW). We show that even idealized measurements of the gas circular motions can lead to the incorrect answer if velocity underestimates induced by pressure support, with a typical size of order $\si